Diagnostic performance of a semiconductor gamma-camera system as studied by multicenter registry. Issue 2 (February 2017) - Chikamori, Taishiro; Goto, Kenji; Hida, Satoshi; Miyagawa, Masao; Ishimura, Hayato; Uchida, Kenji; Fukuyama, Takaya; Mochizuki, Teruhito; Yamashina, Akira
Abstract: Background: Despite the introduction of the novel cadmium–zinc–telluride (CZT) single-photon emission computed tomography (SPECT) in Japan; its diagnostic value in clinical practice remains largely unknown. Methods: The Semiconductor SPECT Study group is a multicenter Japanese registry which registered 1000 patients to evaluate the diagnostic utility of the CZT camera system (Discovery NM530c; GE Healthcare, Haifa, Israel). The patients underwent stress myocardial SPECT and coronary angiography within a 3-month interval. A significant stenosis was defined as ≥75% diameter narrowing based on the American Heart Association classification. Results: Technetium ( 99m Tc) radiotracer (555–1110 MBq) was used in 71% and thallium-201 ( 201 Tl) (74–148 MBq) in 29%. The scan times with 99m Tc-radiotracer were 5–10 min for stress and 3–10 min for rest, whereas those with 201 Tl were 5–9 min for stress and 8–10 min for rest. To detect individual coronary stenosis, the respective sensitivities, specificities, and accuracies were 74%, 85%, and 81% for left anterior descending coronary artery (LAD) stenosis, 76%, 89%, and 85% for left circumflex stenosis, and 72%, 86%, and 82% for right coronary artery stenosis. However, 66% sensitivity and 91% specificity for LAD stenosis were observed with 99m Tc-radiotracer, whereas 88% sensitivity and 63% specificity were found with 201 Tl. Conclusions: The novel CZT SPECT system facilitated a short scan time with reduced radiotracer dose, yielding an acceptable diagnostic performance for angiographical coronary artery disease, although the low sensitivity for LAD detection with 99m Tc-radiotracer needs to be refined.